Establishing reporting standards for participant characteristics in post-stroke aphasia research: An international e-Delphi exercise and consensus meeting - Wallace, Sarah J; Isaacs, Megan; Ali, Myzoon; Brady, Marian C (Clinical rehabilitation, 2023)
To establish international, multidisciplinary expert consensus on minimum participant characteristic reporting standards in aphasia research (DESCRIBE project). An international, three-round e-Delphi exercise and consensus meeting, involving multidisciplinary researchers, clinicians and journal editors working academically or clinically in the field of aphasia. Round 1 of the DESCRIBE e-Delphi exercise ( = 156) generated 113 items, 20 of which reached consensus by round 3. The final consensus meeting ( = 19 participants) established DESCRIBE's 14 participant characteristics that should be reported in aphasia studies: age; years of education; biological sex; language of treatment/testing; primary language; languages used; history of condition(s) known to impact communication/cognition; history of previous stroke; lesion hemisphere; time since onset of aphasia; conditions arising from the neurological event; and, for communication partner participants, age, biological sex and relationship to person with aphasia. Each characteristic has been defined and matched with standard response options to enable consistent reporting. Aphasia research studies should report the 14 DESCRIBE participant characteristics as a minimum. Consistent adherence to the DESCRIBE minimum reporting standard will reduce research wastage and facilitate evidence-based aphasia management by enabling replication and collation of research findings, and translation of evidence into practice.